2009
DOI: 10.3758/app.71.5.1107
|View full text |Cite
|
Sign up to set email alerts
|

Gaze behavior in face comparison: The roles of sex, task, and symmetry

Abstract: Knowing where people look on a face provides an objective insight into the information entering the visual system and into cognitive processes involved in face perception. In the present study, we recorded eye movements of human participants while they compared two faces presented simultaneously. Observers‘ viewing behavior and performance was examined in two tasks of parametrically varying difficulty, using two types of face stimuli (sex morphs and identity morphs). The frequency, duration, and temporal seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 48 publications
6
32
2
Order By: Relevance
“…Memory, attention, language, visuospatial functions, all certainly will have some degree of impairment in when most basic functions are impaired [197][198][199][200][201][202][203][204]. Although there are processing in parallel, in those cases, the hierarchical processing is much stronger and influencer.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Memory, attention, language, visuospatial functions, all certainly will have some degree of impairment in when most basic functions are impaired [197][198][199][200][201][202][203][204]. Although there are processing in parallel, in those cases, the hierarchical processing is much stronger and influencer.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In fact, several investigations have revealed two distinct viewing strategies between participants, even though all participants were instructed equally. In an eye-tracking task requiring participants to judge the femininity of presented stimulus faces (Armann and Bülthoff, 2009) two sub-groups emerged without differential instructions: one group of participants who preferentially fixated on the eye region, and a second group who fixated on the center of the face more often and for longer. Together with participants’ verbal reports, the authors interpreted the group that showed longer and more centralized fixations as a separate, more holistic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore set out to study eye movement patterns during intuitive face judgments, since this methodology is known to “provide an objective insight into the information entering the visual system and into cognitive processes involved” (Armann and Bülthoff, 2009). To this end, we differentially instructed two groups of participants: an “intuitive group,” whom we instructed to judge the authenticity of facial expressions relying on their “gut feeling” and “answering spontaneously.” As well as a “deliberate group,” whom we instructed to judge the authenticity of (the same) facial expressions after careful thought and focusing especially on the eye and mouth region (see Materials and Methods for explicit instructions).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, subjects were overall faster with numerosities compared to faces (Figure 3) but the effect of ratio on RT was similar for both tasks. Since RT is defined as the time between stimulus onset and liftoff, the slower RT for faces can be at least partly explained by differences in how the stimuli are encoded, taking less time for arrays of dots than facial expressions (Armann & Bülthoff, 2009;Cantlon & Brannon, 2006;Stoesz & Jakobson, 2013;Verguts, Fias, & Stevens, 2005;Walker-Smith, 1978). As for accuracy, the slight advantage for faces only on hard ratios may reflect slightly more precise mental representations of facial expressions compared to numerosities -again, an encoding effect.…”
mentioning
confidence: 99%